Interaction between FtsZ and inhibitors of cell division. - Huang, J (1996)
The interaction between inhibitors of cell division and FtsZ were assessed by using the yeast two-hybrid system. An interaction was observed between FtsZ and SulA, a component of the SOS response, and the interacting regions were mapped to their conserved domains. This interaction was reduced by mutations in sulA and by most mutations in ftsZ that make cell refractory to sulA. No interaction was detected between FtsZ and MinCD, an inhibitory component of the site selection system. However, interactions were observed among various members of the Min system, and MinE was found to reduce the interaction between MinC and MinD. The implications of these findings for cell division are discussed.